The Effect of Debt to Equity Ratio and Total Asset Turnover on Return On Asset in Property and Real Estate Sub-Sector Companies Listed on the Indonesia Stock Exchange in the Period 2021-2023 - Mardiyani, Mardiyani; Komara, Acep; Adella, Resso Panji; Audah, Taufan (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: The research effort is designed to assess the interdependency among the variables specifically, the Debt-to-Equity Ratio (DER) and Total Asset Turnover (TATO) to establish their collective impact on the dependent variable, Return on Assets (ROA). The scope is limited to an examination of financial data from IDX-listed property and real estate entities throughout the three-year timeframe between 2021 and 2023. Design/methodology/approach: The research employed SPSS (version 26) to conduct the necessary preliminary analyses. These included checks for normality, autocorrelation, multicollinearity, and heteroscedasticity, which are the standard statistical assumptions. The study's hypotheses were evaluated through multiple linear regression analysis, incorporating necessary t-tests and F-tests. The choice of a purposive sampling method was justified on the grounds that it enables the inclusion of only those samples that are most relevant and directly contribute to addressing the specific aims of the investigation. Findings: A powerful statistical association was identified, indicating that the Return on Assets (ROA) is largely contingent upon the interplay between a firm's Debt-to-Equity Ratio (DER) and its Total Asset Turnover (TATO). This implies that strategic financial decisions such as managing debt to enhance asset utilization and fulfill financial commitments, as indicated by DER, and maximizing revenue and profit generation from assets, as represented by TATO play a direct role in shaping ROA, which serves as a critical indicator of a firm's profitability. Research limitations/implications: Data collection was strictly confined to the 2021–2023 observation timeframe, with figures sourced entirely from property and real estate firms trading on the Indonesia Stock Exchange (IDX). As a consequence of this focus, the generalizability of the results is inherently constrained; the findings may not be reliably applied to other industrial sectors or alternative time periods. This methodological limitation stems from the acknowledged variance in financial structures, operational models, and distinct market environments that differentiate industries and change significantly across historical eras. Practical implications: The study's findings can serve as a foundation for financial decisions made by investors and business management, especially when it comes to controlling debt and actions that boost profitability. Originality/value: The findings from this investigation are anticipated to enhance academic understanding of managerial performance, particularly by detailing how Debt-to-Equity Ratio (DER) and Total Asset Turnover (TATO) exert influence on Return on Assets (ROA) specifically among property and real estate companies. Paper type: Research Paper